Feasibility study of the fuel card system, a case of Sakunda energy - Chibanda, Darius M. (Midlands State University, 2017)
Sakunda Energy has been facing declining revenue for the past three years. The company was using the fuel coupons as a way of managing its revenue and the fuel coupon was causing the company to suffer losses in revenue. The fuel coupons had problems which include recyclability and vulnerability to theft of the coupons. This resulted in the company introducing the fuel card system as a way to mitigate these shortcomings. The newly implemented was put to use but there seems to be persistent decline in revenue. This highlighted the problem which was being encountered by Sakunda Energy. This research paper examines the coupon system, examines the fuel card system, evaluates the system implementation guidelines in place, analyses the controls put in place and finally evaluates the best revenue management system at Sakunda Energy. The researcher used descriptive research design because of the nature of the company. Tools that were used by the researcher include questionnaires and interviews. The study also analyses data obtained and the researcher concluded the research by explaining the best revenue management that should be practised by Sakunda Energy.